Barreras de acceso a los servicios de salud bucodental en poblaciones Indígenas del Perú - Salazar-Villavicencio, Alisson (2025)
Oral diseases affect millions of people worldwide, with greater disparities in low- and middle-income countries, where access to oral health services is limited for some population groups. In Latin America, dental caries is particularly prevalent. Indigenous populations face additional challenges due to social determinants such as poverty. The objective of this article is to present an analysis of the possible barriers to access to oral health services faced by indigenous populations in Peru, as well as to provide recommendations for addressing them.